Efficacy of Entecavir in Chronic Hepatitis B Patients with Persistently Normal Alanine Aminotransferase: Randomized, Double-Blind, Placebo-Controlled Study. Issue 8 (November 2014) - Tseng, Kuo-Chih; Chen, Chi-Yi; Tsai, Hung-Wen; Chang, Ting-Tsung; Chuang, Wan-Long; Hsu, Ping-I; Liu, Wen-Chun; Cheng, Pin-Nan
Background: It is still inconclusive whether chronic hepatitis B (CHB) patients with persistently normal alanine aminotransferase (PNALT) should receive nucleoside/nucleotide analogues. This study is to evaluate the efficacy of entecavir in improving liver histology in CHB patients with PNALT. Methods: In this prospective randomized, double-blind, placebo-controlled study, 380 CHB patients with PNALT were screened, 82 patients received biopsy and 43 patients met the HBV DNA and histology criteria and were randomly assigned to either an entecavir or placebo group for 52 weeks, with 22 and 21 in each group, respectively. The primary objective was to evaluate histological improvement. The secondary objective is to evaluate virological efficacy. Results: A total of eight (38.1%) patients in the entecavir group and eight (44.4%) in the placebo group ( P =0.752) showed histological improvement. The decrease in total Knodell scores (±sd ) was 1.3 ±1.9 in the entecavir group and 1.5 ±2.2 in the placebo group ( P =0.803). The subjects with undetectable HBV DNA at week 52 were 16/21 (76.2%) in the entecavir group and 0/18 (0%) in the placebo group ( P <0.001). The mean HBV DNA reduction from baseline to week 52 was 4.73 ±0.83 in the entecavir and 0.25 ±0.81 in the placebo group ( P <0.001). Conclusions: CHB patients with PNALT receiving entecavir therapy for one year achieved virological efficacy, but not histological benefit. ClinicalTrials.gov number NCT01833611.